COMPARISON OF MODEl PREDICTIONS AND SPEED TRIAL RESULTS fOR A GROUP Of 32’ WOODEN TRAWLERS - RAJENDRAN, R; SAIN, V (Fishery Technology, 2025)
Speed trial results of six 32’ wooden sternÂ· trawlers built to the same design are analysed to determine the EHP ship– Froude number curves in each case .and are compared with the model test results of the same design and for the corresponding displacement conditions